Cerebral blood flow and BOLD fMRI responses to hypoxia in awake and anesthetized rats - Duong, Timothy Q. (2007)
This study investigated the functional MRI responses to graded hypoxia in awake/restrained and anesthetized animals by measuring cerebral blood flow (CBF) and blood oxygenation (BOLD) changes and estimating changes in cerebral metabolic rate of oxygen (CMRO(2)). Hypoxia in isoflurane anesthetized rats reduced blood pressure but did not change heart rate and respiration rate. In contrast, hypoxia in awake animals showed compensatory responses by sustaining blood pressure, increasing heart rate and respiration rate. Basal CBF was higher under isoflurane anesthesia than awake state because isoflurane is a vasodilator. Graded hypoxia decreased BOLD signals. Surprisingly, hypoxia also decreased CBF likely because hypoxia induced hypocapnia. Hypoxia-induced CBF and BOLD decreases were smaller in awake, relative to anesthetized, rats at low pO(2), but similar at high pO(2). CBF leveled off with decreasing hypoxia-induced pCO(2) in awake rats, but monotonically decreased in anesthetized rats. CMRO(2) estimated using a biophysical BOLD model did not change under mild hypoxia but was reduced under severe hypoxia relative to baseline. These results showed that isoflurane attenuated automomic responses to hypoxia, hypoxia-induced hypocapnia dominated CBF changes, tissues in awake conditions appeared better oxygenated, and severe hypoxia reduced oxygen metabolism. This study underscored the marked differences in BOLD and CBF MRI responses to hypoxia in vivo between awake and anesthetized conditions and has implications for functional MRI studies of hypoxia in anesthetized animal models.